Nilai-Nilai Pendidikan Akhlak Dalam Al-Qur'an Surat Al-Hujurat Ayat 11-13 (Perbandingan Tafsir Ibnu Katsir Dan Tafsir Al-Misbah) - Rosna Wati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Sakinah Dharmasraya, 2022)
The research of this thesis is motivated by the problems that occur in society who commit disgraceful acts that make the moral decline of the nation's children in daily life, in people's lives there are still many disgraceful acts, such as gossiping, making fun of, criticizing, prejudice and others. -other. So the need for educators both in the community and schools to educate on good behavior in accordance with Law No. 20 of 2003 concerning the National Education System, article 3, in fact national education is currently less able to apply morality. Therefore, researchers are interested in how the values ​​of moral education contained in Surah Al-Hujurat verses 11-13 in 2 comparisons of interpretation between Tafsir Ibn Katsir and Al-Misbah. This type of research is using qualitative research methods literature (Library research). The researcher describes the values ​​of moral education in Surah Al-Hujurat verses 11-13 in the interpretations of Ibn Kathir and Al-Misbah. To collect data the author uses the documentation method, namely collecting references related to the title of the researcher, including also collecting data that already exists on internet media such as social media, articles and non-internet such as newspapers and magazines. Before the researcher enters the data, the researcher conducts Content Analysis, which is analyzing various documentation/references and focusing on the subject to be studied by selecting certain sentences, themes, traits and words. Then the researcher compared the contents of Surah Al-Hujurat: 11-13 from the interpretations of Al-Ibn Katsir and Al-Misbah. Katsir, prohibition of criticizing and insulting others, prohibition of calling with a bad call, prohibition of prejudice, prohibition of finding fault with others, prohibition of giving and commands of repentance, orders to know each other, connecting kinship ties and commands of piety. In the interpretation of Al-Misbah, avoiding conflict by not making fun of one another, not self-deprecating, not giving bad titles, not giving gifts, commands of piety.